Determinant of Stock Price Volatility in LQ45 Companies: An Analysis of Macroeconomic Conditions In Indonesia - Djazuli, Abid; Lestriyani, Desi (Jurnal Ilmu Manajemen, 2021)
The capital market is one of the indicators used in assessing the economic conditions of a country. This research was conducted with the aim of knowing and analyzing the effect of exchange rates and SBI interest rates on stock price volatility at LQ45 companies. Sampling using purposive sampling, the sample used was 19 companies. The data required is secondary data obtained from company reports published on the Indonesia Stock Exchange website and the data collection method is using the documentation method. The analysis technique used in this research is multiple regression analysis. The results of the F test show that there is a significant effect of the Exchange Rate and the SBI Interest Rate on the Volatility of Stock Prices. The results of the t test show that there is a significant effect of Exchange Rate on Stock Price Volatility and SBI Interest Rates, indicating that there is no significant effect on Stock Price Volatility in LQ45 companies. The results of this analysis can be used as information for companies listed on the Indonesian stock exchange to be able to determine the stock price accurately, which can benefit all parties.